(untitled) (Nigerian Journal of Technology, 2015)
The assimilative capacity of a water body requires knowledge of the river characteristics, pattern of effluent loading, river hydraulic resilience and far-field mixing to effectively determine it, hence it is considered appropriate that diverse models and approaches are utilized in its determination’’. This study evaluated the assimilative capacity of Ikpoba River using different approaches namely: homogeneous differential equation, ANOVA/Duncan Multiple rage test, first and second order differential equations, correlation analysis, Eigen values and eigenvectors, multiple linear regression, bootstrapping and far-field mixing Analytics. In the rainy, dry, and harmattan seasons the values of assimilative capacity for Guinness, Ewa road and UBTH point sources of effluent discharge are as follows: 1.07 x 1010kg/day, 1.07 x 1010kg/day and 1.29x1010kg/day; 8.1x109kg/day, 9.07x109kg/day and 1.05x 1010kg/day;1.28x1010kg/day, 1.03x109kg/day and 1.95x1010kg/day in that order. It was also discovered that by model tricking, assimilative capacity had a range of values that varied from 231.09mg/l upper limit to -222.27mg/l lower limit at 95%significance level and beyond this range, the model developed will breakdown, and its robustness weakened by poor predictive capacity. The upper control limit for each of the various pollutants considered indicates the saturated value of the dissolved oxygen (DO), and the negative lower control limits depict dissolved oxygen debt whereby the DO falls below critical (anoxia) to harsh critical level. At this level any reaeration or reoxygenation effort is not practically palpable until recovery is made up to critical level. The eclectic approaches adopted have crossed the stream where it is shallowest. http://dx.doi.org/10.4314/njt.v35i1.27